1996
DOI: 10.1007/bf00187473
|View full text |Cite
|
Sign up to set email alerts
|

Development and ageing of the articular cartilage of the rabbit knee joint: distribution of the fibrillar collagens

Abstract: The development of the articular cartilage of the rabbit knee joint from the 17-day fetus to the 2-year adult rabbit has been examined. At 17 days, the developing femur and tibia are separated by the interzone. Cavitation occurs around 25 days; the cells of the intermediate layer flatten and move onto those of the chondogenous layers to create the articular surfaces. After birth, growth of the cartilage is mainly the result of matrix production. Ossification of the epiphyses is complete by 6 weeks postpartum. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
57
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 37 publications
6
57
0
Order By: Relevance
“…The identification of type V collagen in the matrix around the putative chondrocytes in the chondrogenous layers of developing joints Ashhurst 1996 and2001) showed that these cells are unique and distinct from the chondrocytes of epiphyseal cartilage. Since that time further distinctive features have emerged.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The identification of type V collagen in the matrix around the putative chondrocytes in the chondrogenous layers of developing joints Ashhurst 1996 and2001) showed that these cells are unique and distinct from the chondrocytes of epiphyseal cartilage. Since that time further distinctive features have emerged.…”
Section: Discussionmentioning
confidence: 99%
“…This antibody was affinity purified. Its primary reactivity is against the α2 chain of type V collagen, but it shows low reactivity against the α2 chain of type XI collagen (Bland and Ashhurst 1996).…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…Both the predominant orientation in the collagen network and the amount of collagen in the network affect the mechanical behaviour, and thus the functioning, of AC [15-18]. The collagen network remodels between birth and maturity: the adult depth-dependent structure is absent at birth [19-23], collagen type I is replaced by collagen type II [24-26], and collagen densities increase [27-29] with depth-dependent variation [21]. …”
Section: Introductionmentioning
confidence: 99%